Uma análise do ethos no discurso publicitário da L'Oréal Paris - Blasques, Fernanda (2007)
The research here developed has had the intention of showing the build up of the ethos in the advertising speech of L Oréal through the analysis of advertising pieces propagated in the printed media in the year 2006.Studied since Aristotle s Rhetoric until our times through the Speech Analysis and authors as Maingueneau and Charaudeau, the ethos takes part into the formation of the enunciative scene, also built by aspects the place and time of the articulation, social condition of the speaker and the listener of the message and the situation in which the speech is being produced. As the ethos is the voice of the speech, it makes interdependent all the other relevant elements for the building of the scene. To achieve the objective, we start by pointing out the definition and presentation of concepts referring to the Speech Analysis (more specifically about the ethos) according to the works of Charaudeau (2006) e Maingueneau (1997, 1999 e 2002), and to aspects of the advertising language according to Carvalho (2003), Carrascoza (2003) and Priore (2000). The considerations about Ideology retake authors as Althusser (1998), Bakhtin (1990) and Neto (1999); theoretic aspects about ethos, rhetoric and persuasion in the works of Aristóteles (199_ e 2000), Maingueneau e Charaudeau. In the analysis, the advertisings were described in their image aspects; after that, they were studied in relation to their speech and ideological formation, and, finally, according to the message transmitted by the speaker of the ethos. As the result, it was verified that, independently of the product announced or the kind of public to be achieved by the speech of the speaker, the same ethos is kept trying to offer the consumers something that may be able to resolve an important problem for the modern women: the necessity of eternal beauty and youth, which are values imposed by the current Ideology. For this to be possible, the speaker of the ethos of L Oréal Paris uses famous models (who posses the values desired for modern women) to give authority to the advertisings. So the ethos suggests always that common women can also become beautiful and young as the stars in the ads.